Seasonal insect migrations: massive, influential, and overlooked. Issue 6 (8th June 2020) - Satterfield, Dara A; Sillett, T Scott; Chapman, Jason W; Altizer, Sonia; Marra, Peter P
Abstract : During seasonal changes around the globe, trillions of insects are on the move. Many insect populations, including butterflies, moths, hoverflies, and dragonflies, make repeated seasonal migrations each year. It is only during the past century that biologists have come to accept the concept of insect migration, and new research using radar, citizen science, and stable isotopes has revealed unexpected insights about this phenomenon. Drawing on these findings, we demonstrate how seasonal insect movements are both massive and ecologically influential, with consequences for food webs, nutrient transport, pollination, and infectious disease. Responding to environmental changes, some mobile insect populations are declining or shifting the timing and extent of their journeys. We suggest research and policy priorities for investigating and protecting insect migrations. Outcomes from such work could transform strategies for agricultural pest control and wildlife conservation, and could help preserve the ecological functions performed by migratory insects.